DIGITAL GAME BASED LEARNING DENGAN MODEL ADDIE UNTUK PEMBELAJARAN DOA SEHARI - HARI - Galang Prihadi Mahardhika (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
Dua is one of the most important praying in Islam. It's such an obligatory for each moslem to perform dua before and after doing activities. Since there are many kinds of dua in Islam (e.g. dua before and after eating, dua before sleep and when wake up in the morning, dua before studying, etc), it is important for moslem to learn dua in early childhood education. Kemendiknas RI (The Ministry of National Education of the Republic of Indonesia) have published a policy which states that dua is a compulsory subject in early childhood education. Herlina et al (2014) found that learning dua will be more effective by practicing it in daily life activities. This paper discuss about enacting Digital Game Based Learning (DGBL) to improve the learning method to help students in early chidlhood education to learn dua. DGBL method is applied by developing a digital story telling application using Analyzing, Designing, Developing, Implementing, and Evaluating (ADDIE) model. This application provides stories which give information about dua in student's daily life activities.